A systematic investigation on the response of EBT-XD gafchromic films to varying dose-per-pulse, average dose-rate and instantaneous dose-rate in electron flash beams - Del Sarto, D.; Masturzo, L.; Cavalieri, A.; Celentano, M.; Fuentes, T.; Gadducci, G.; Giannini, N.; Gonnelli, A.; Milluzzo, G.; Paiar, F.; Pensavalle, J. H.; Romano, F.; et al. (Frontiers in Physics, 2025)
BackgroundThe FLASH effect is a radiobiological phenomena characterized by the reduction of the damage to healthy tissues while maintaining iso-effectiveness on the tumour, obtained by delivering the entire radiation dose in less than 100–200 m and with average dose rate greater than 40–100 Gy/s. Despite the enormous interests of the scientific community, a series of issues must be addressed and overcome to reach its clinical implementation. One of these challenges is related to the dosimetry of ultra-high dose-per-pulse (UHDP) beams, which trigger the effect. The most used dosimeters to date in radiobiological experiments with ultra-high dose rate (UHDR) beams are the radiochromic films. However, a systematic and accurate study of their response by varying dose-per-pulse and dose rate over a wide range has never yet been done.PurposeTo systematically investigate the response of EBT-XD radiochromic films under UHDR electron beam irradiations by varying different beam parameters independently and over a wide range and using flashDiamond as reference.Materials and MethodsThanks to a special research linac, average dose rate (ADR), dose-per-pulse (DP) and instantaneous dose rate (IDR) dependencies on film response have been individually investigated. The reference value of ADR, DP and IDR has been calculated by measuring the dose using a flashDiamond and knowing the temporal beam structure provided by the beam monitoring system of the Linac.ResultsOur results normalized to fD showed an overresponse of the radiochromic films, compared to a conventional irradiation, for ADR values higher than 1000 Gy/s and an IDR higher than 1 MGy/s which could represent a total dose overestimation of about 10%.DiscussionThe gafchromic film EBT-XD have their field of application in UHDP beam dosimetry, considering their excellent spatial resolution; However, particular attention must be paid when using this type of dosimeter for absolute dose measurements at very extreme values of IDR (>1 MGy/s).